2009
DOI: 10.22358/jafs/66379/2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ligninolytic potential of <i>Phlebia</i> species and their role in improvement of <i>in vitro</i> digestibility of wheat straw

Abstract: Digestibility of crop-residues can be enhanced by the delignifi cation, which improves its nutritive quality. Presence of lignin in these crop-residues which act as digestibility barrier can be degraded by fungi. The biodelignifi cation ability of three Phlebia species: Phlebia radiata, Phlebia fascicularia and Phlebia brevispora, was studied under solid state fermentation of wheat straw for 30 days and compared with that of much studied white rot fungus Ceriporiopsis subvermispora. Different parameters includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
0
33
1
1
Order By: Relevance
“…White-rot fungi use enzymatic mechanisms to break down lignin, alter lignocellulose structures, and improve the nutritive value of low quality feeds, which has been widely reported using rape straw (Tripathi et al 2008), wheat straw (Tuyen et al 2012), rice straw (Sharma and Arora 2010), corn stover (Tuyen et al 2013), and sugarcane bagasse (Tuyen et al 2013). However, the accompanied losses of cellulose and hemicellulose are often very high during the degradation of these materials using some white rot fungi, which limits their practical use and necessitates looking towards selective ligninolytic organisms (Arora and Sharma 2009). Tuyen et al (2013) found that Ceriporiopsis subvermispora and Lentinula edodes were highly selective for lignin over cellulose and had a particularly high potential to improve the nutritive value of highly lignified ruminant feeds, such as rice straw, oil palm fronds, and sugarcane bagasse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…White-rot fungi use enzymatic mechanisms to break down lignin, alter lignocellulose structures, and improve the nutritive value of low quality feeds, which has been widely reported using rape straw (Tripathi et al 2008), wheat straw (Tuyen et al 2012), rice straw (Sharma and Arora 2010), corn stover (Tuyen et al 2013), and sugarcane bagasse (Tuyen et al 2013). However, the accompanied losses of cellulose and hemicellulose are often very high during the degradation of these materials using some white rot fungi, which limits their practical use and necessitates looking towards selective ligninolytic organisms (Arora and Sharma 2009). Tuyen et al (2013) found that Ceriporiopsis subvermispora and Lentinula edodes were highly selective for lignin over cellulose and had a particularly high potential to improve the nutritive value of highly lignified ruminant feeds, such as rice straw, oil palm fronds, and sugarcane bagasse.…”
Section: Introductionmentioning
confidence: 99%
“…Tuyen et al (2013) found that Ceriporiopsis subvermispora and Lentinula edodes were highly selective for lignin over cellulose and had a particularly high potential to improve the nutritive value of highly lignified ruminant feeds, such as rice straw, oil palm fronds, and sugarcane bagasse. Phlebia species including P. brevispora, P. radiate, and P. fascicularia have also been reported to be highly selective for lignin degradation and possess the potential capability for improvement of digestibility of agricultural by-products (Arora and Sharma 2009;Sharma and Arora 2010). However, very limited data on the effect of these fungi on the chemical composition and degradability of rape straw have been published.…”
Section: Introductionmentioning
confidence: 99%
“…So, lignin has to be degraded for the digestibility in the rumen to occur. However, rumen microorganisms are inadequate in degrading this hard structure [25]. To that end, a plurality of delignification studies has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Adv., 10 (5): 237-246, 2015 24%. While, many researches reported that, the biological treatments of crop residues tend to increase nutrients digestibility (Chen et al, 1995;Akinfemi et al, 2009;Arora and Sharma, 2009). This variability in responses to the biologically treated materials feeding is due to that different condition, such as ration formula, using another source of roughage material and level of concentrate roughage ratio (El-Bordeny et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Due to high shortage of conventional fodders especially in arid and semi-arid areas such as Egypt, the big feed gap between the requirements and the available sources necessitates great efforts to realize the best utilization of the available feed resources. During the last years, many efforts have been employed to increase their feeding values by biological treatments (Liu and Orskov, 2000;Zhu et al, 2005;Eun et al, 2006), which many studies indicated that the biological treatments tend to increase in vitro digestibility of tested materials (Zadrazil and Puniya, 1995;Sharma and Arora, 2010) and in vivo digestibility (Chen et al, 1995;Akinfemi et al, 2009;Arora and Sharma, 2009). Moreover, Fazaeli et al (2004), Kabirifard et al (2007), Omer et al (2012), Shrivastava et al (2012) and El-Bordeny et al (2015) reported a positive response in terms of nutrient utilization, nitrogen balance as well as body weight gain associated with using of biologically treated crop residues in animal feeding.…”
Section: Introductionmentioning
confidence: 99%